Research on properties of basalt fiber-reinforced asphalt mastic - Shi, Chenglin; Wang, Jianan; Sun, Shuang; Lv, Dongye; Xu, Lina; Zhang, Sufeng (Frontiers in Materials, 2023)
A basalt fiber-reinforced asphalt mixture can improve the engineering properties of asphalt pavement and prolong the service life of the road. However, few studies have systematically examined the composition of asphalt mixtures or the optimal ratio of fiber asphalt mastic suitable for different structural types. The effects of fiber content, filler–asphalt ratio, and asphalt viscosity on the properties of fiber asphalt mastic were investigated by orthogonal experiments to explore the reinforcement effect of basalt fiber on asphalt mastic. The optimal ratio of fiber asphalt mastic suitable for gap-graded and dense-graded asphalt mixtures was obtained by the fuzzy comprehensive evaluation (FCE) method. Meanwhile, the reinforcement effects of bundled basalt fiber (BBF), flocculated basalt fiber (FBF), polyester fiber (PF), and lignin fiber (LF) on asphalt mastic were compared and analyzed based on the optimal ratio of FBF asphalt mastic. The results showed that the optimal fiber asphalt mastic ratio suitable for gap-graded and dense-graded asphalt mixtures were that fiber content, filler–asphalt ratio, and asphalt viscosity were 3%, 1.8, and 1.1 Pa·s and 2%, 1.0, and 0.7 Pa·s, respectively. Analyzing the properties of different types of fiber asphalt mastic revealed that FBF could effectively enhance the high-temperature rheological properties and low-temperature tensile properties of asphalt mastic compared with other fibers. FBF asphalt mastic improved the asphalt rutting factor by more than four times. The tensile fracture energy of fiber asphalt mastic was more than three times that of the corresponding asphalt. The reinforcement effect of BBF was poor; it was recommended to be broken up before use.